Społeczeństwo Galii V w. wobec migracji barbarzyńskich w świetle łacińskiej literatury patrystycznej - Maciej Wojcieszak (In Gremium. Studies in History, Culture and Politics, 2025)
In the 5th century, the western part of the Roman Empire was falling apart. That was due to barbarian migrations, usurpations, internal conflicts and crises such as the growth of the Empire, barbarization in the administration and army and religious disturbances, which increased with christianization. Each of these issues had a big impact on society at that time. Late antiquity represented the metaphorical and literal end of the world as the Romans knew it. In the article, I analyzed the aspect of barbarian migrations and their impact on the attitudes of Gallic society in the 5th century. The analysis was made in the light of latin patristic literature of the 5th century. I discussed society's attitudes and behavior in the face of barbarian migrations. I discussed these issues problematically, considering issues such as: the prevailing fear of invaders, impoverishment of all social classes in Gaul as a result of barbarian migrations, escaping to other parts of the Empire from the barbarians, fear of losing Roman culture (e.g. language, traditions, customs), concern for the preservation of the catholic (nicene) faith in the face of the occupation of Gaul by barbarians supporting the Arians faith or problems that arose after migrations, when it was necessary to return to „normality” and continue living, this time among new neighbors. This is the image of society presented by christian authors. The problem in the sources was that the authors rarely focused on the lower social classes, primarily describing the higher ones (most of which they came from), which is reflected in the article. Moreover, the analyzed sources are specific because their authors wrote mainly in a didactic and pastoral way. Often used rhetorical exaggerations were intended to draw the attention of the faithfuls to a given problem and persuading them to change their behavior and improve. Despite their shortcomings, the sources I used are among the most important literary sources for the economic, political and social history of the Roman Empire in late antiquity.